Investigating the toxicity and safety of radiotherapy for pancreatic cancer - Holyoake, D (2018)
The current level of understanding of the relationship of gastrointestinal toxicity with irradiation of the stomach, duodenum, and small bowel hampers the potential of radiotherapy to contribute effectively to achieving disease control for patients diagnosed with pancreatic cancer. The work in this thesis aimed to further this understanding through compilation and examination of existing informative data, and robust analysis of this relationship within a large cohort of patients treated with radiotherapy to the pancreas, and within a new clinical trial of stereotactic radiotherapy (SBRT). A systematic literature review was undertaken and publications were identified that found dose-volume parameters for the stomach (V20Gy, V50Gy, D2cm3), duodenum (V25Gy-V55Gy) and small bowel (V40Gy, V50Gy, D2cm3) to be predictive of toxicity in pancreatic cancer. Parameters were fitted for the Lyman-Kutcher-Burman normal tissue complication probability model for the duodenum, using published cohort dose-volume histograms and the associated incidence of toxicity. Results were consistent with previous analyses, showing a dependence on exposure to high dose and small volume effect. Published small bowel dose-volume histogram data was incorporated into meta-analysis and showed that, for rectal cancer, a significant volume effect exists for all clinically relevant doses (5 Gy to 50 Gy). This was not seen in data regarding irradiation for gynaecological cancer, where a volume effect was only observed at higher doses (40 Gy and over). This difference is thought to be primarily due to the concomitant chemotherapy used in the treatment of these malignancies. Analysis of the toxicity outcomes for patients treated in the phase-II trials ARCII and SCALOP identified stomach dose-volume parameters predictive of acute gastrointestinal toxicity on multivariable analysis, alongside patient sex and the concomitant chemotherapy regimen utilised. Use of a statistical technique novel to radiotherapy dose-volume analysis was explored (canonical correlation) but was not shown to be superior to existing techniques. Pre-trial radiotherapy quality assurance for the SPARC clinical trial of pre-operative SBRT was undertaken and found evidence of over-generous clinician contouring in definition of the primary tumour target volume. This was shown to have implications for modelled risk of treatment toxicity, however contouring improved with education and feedback from peers. In conclusion, intensification of pancreatic cancer radiotherapy is likely to be safe and acceptable for patients, provided that dose to the neighbouring organs of the upper gastrointestinal tract is managed. This may be achieved through accurate target definition and optimisation of the treatment process with control of patient motion and image-guided intensity-modulated radiotherapy or SBRT. Concomitant chemotherapy is shown to be an important modifier of the radiotherapy dose-volume-toxicity relationship.